Drug resistance profile and clonality of Plasmodium falciparum parasites in Cape Verde - Da Veiga Leal, Silvania (2021)
BACKGROUND: Cape Verde is an archipelago located off the West African coast and is in a pre-elimination phase of malaria control. Since 2010, fewer than 20 Plasmodium falciparum malaria cases have been reported annually, except in 2017, when an outbreak in Praia before the rainy season led to 423 autochthonous cases. It is important to understand the genetic diversity of circulating P. falciparum to inform on drug resistance, potential transmission networks and sources of infection, including parasite importation. METHODS: Enrolled subjects involved malaria patients admitted to Dr Agostinho Neto Hospital at Praia city, Santiago island, Cape Verde, between July and October 2017. Neighbours and family members of enrolled cases were assessed for the presence of anti-P. falciparum antibodies. Sanger sequencing and real-time PCR was used to identify SNPs in genes associated with drug resistance (e.g., pfdhfr, pfdhps, pfmdr1, pfk13, pfcrt), and whole genome sequencing data were generated to investigate the population structure of P. falciparum parasites. RESULTS: The study analysed 190 parasite samples, 187 indigenous and 3 from imported infections. Malaria cases were distributed throughout Praia city. There were no cases of severe malaria and all patients had an adequate clinical and parasitological response after treatment. Anti-P. falciparum antibodies were not detected in the 137 neighbours and family members tested. No mutations were detected in pfdhps. The triple mutation S108N/N51I/C59R in pfdhfr and the chloroquine-resistant CVIET haplotype in the pfcrt gene were detected in almost all samples. Variations in pfk13 were identified in only one sample (R645T, E668K). The haplotype NFD for pfmdr1 was detected in the majority of samples (89.7%). CONCLUSIONS: Polymorphisms in pfk13 associated with artemisinin-based combination therapy (ACT) tolerance in Southeast Asia were not detected, but the majority of the tested samples carried the pfmdr1 haplotype NFD and anti-malarial-associated mutations in the the pfcrt and pfdhfr genes. The first whole genome sequencing (WGS) was performed for Cape Verdean parasites that showed that the samples cluster together, have a very high level of similarity and are close to other parasites populations from West Africa.